Sistema informático web de matriculación de estudiantes en el Colegio Nacional Técnico Agropecuario Carlos Pomerio Zambrano de Canuto del cantón Chone - Ormaza Medina, Roberto Carlos (2012)
In order to optimize the process of students receiving data the authors of the thesis Roberto Carlos Medina Ormaza and Querubin Mariano Rodriguez Mendoza made and implemented a web computer system for the registration of students in the national Agricultural Technical School "Carlos Zambrano Pomerio" before obtaining an engineering degree in computer science and according to the regulations based on the ESPAM MFL, for this purpose we used the development methodology for web information system, MIDAS. The SD phase, helped get the information through the Flow Diagram Process (FDP) which allowed to obtain the requirements of the user, the HT phase was used to define the interface of the web application, the DB phase served to design the database to organize better the information system through MySqlWorkBench 5.2CE tools, and MySQL 5.5 and finally the FC phase gave dynamic functionality to the Web application by using structured programming and HPP (HyperText Pre-Processor). The publication of the Web application on the internet allowed us to validate the same, generating satisfactory results as reduced time in the process of the student enrollment in the mentioned institution.